The Impact of Computed Tomography on Decision Making in Tibial Plateau Fractures - Castiglia, Marcello Teixeira; Nogueira-Barbosa, Marcello Henrique; Messias, Andre Marcio Vieira; Salim, Rodrigo; Fogagnolo, Fabricio; Schatzker, Joseph; Kfuri, Mauricio (The Journal of Knee Surgery, 2018)
Schatzker introduced one of the most used classification systems for tibial plateau fractures, based on plain radiographs. Computed tomography brought to attention the importance of coronal plane-oriented fractures. The goal of our study was to determine if the addition of computed tomography would affect the decision making of surgeons who usually use the Schatzker classification to assess tibial plateau fractures. Image studies of 70 patients who sustained tibial plateau fractures were uploaded to a dedicated homepage. Every patient was linked to a folder which contained two radiographic projections (anteroposterior and lateral), three interactive videos of computed tomography (axial, sagittal, and coronal), and eight pictures depicting tridimensional reconstructions of the tibial plateau. Ten attending orthopaedic surgeons, who were blinded to the cases, were granted access to the homepage and assessed each set of images in two different rounds, separated to each other by an interval of 2 weeks. Each case was evaluated in three steps, where surgeons had access, respectively to radiographs, two-dimensional videos of computed tomography, and three-dimensional reconstruction images. After every step, surgeons were asked to present how would they classify the case using the Schatzker system and which surgical approaches would be appropriate. We evaluated the inter- and intraobserver reliability of the Schatzker classification using the Kappa concordance coefficient, as well as the impact of computed tomography in the decision making regarding the surgical approach for each case, by using the chi-square test and likelihood ratio. The interobserver concordance kappa coefficients after each assessment step were, respectively, 0.58, 0.62, and 0.64. For the intraobserver analysis, the coefficients were, respectively, 0.76, 0.75, and 0.78. Computed tomography changed the surgical approach selection for the types II, V, and VI of Schatzker (p < 0.01). The addition of computed tomography scans to plain radiographs improved the interobserver reliability of Schatzker classification. Computed tomography had a statistically significant impact in the selection of surgical approaches for the lateral tibial plateau.
Keywords: tibial plateau; fracture; classification; computed tomography; decision making